Diagnostic Performance of PET/CT Using 18F-FACBC in Prostate Cancer: A Meta-Analysis - Bin, Xu; Yong, Shan; Kong, Qing-Fang; Zhao, Sun; Zhang, Guang-Yuan; Wu, Jian-Ping; Chen, Shu-Qiu; Zhu, Wei-Dong; Pan, Ke-Hao; Du, Mu-Long; Chen, Ming (Frontiers in Oncology, 2020)
Background: Diagnostic performance of PET/CT using 18F-fluciclovine (18F-FACBC) in patients with prostate cancer has been evaluated in only a few studies. There is no consensus on the diagnostic value of 18F-FACBC PET/CT in prostate cancer recurrence or metastasis (except for bone metastasis), the primary diagnosis of the lesion. Hence, a meta-analysis was conducted to evaluate the performance of 18F-FACBC PET/CT. Methods: The literature published from June 2015 to June 2019 on using 18F-FACBC PET/CT for the diagnosis of prostate cancer was retrieved on PubMed and EMBASE. Pooled sensitivity (Sen), specificity (Spe), positive and negative likelihood ratios (LR+ and LR-), area under curve (AUC), and diagnostic odds ratio (DOR) of 18F-FACBC PET/CT in patients with prostate cancer were calculated. An SROC map was made and meta-regression analysis carried out. A Fagan plot and likelihood ratio dot plot were drawn. Sensitivity and funnel plot analysis were made. Meta-disc, Review Manager 5.3, and STATA 13 was use for meta-analysis. Results: A total of nine articles met the strict criteria for diagnostic meta-analysis, which included 363 patients and 345 lesions. Pooled Sen, Spe, LR+, LR-, DOR were 0.88, 0.73, 3.3, 0.17, and 20, respectively. Lesions detected on the PET/CT image included primary lesions and metastases. Conclusion: This study comprehensively evaluated the diagnostic value of 18F-FACBC PET/CT on prostate cancer. Our analysis suggests that 18F-FACBC PET/CT is a valuable agent in diagnosing prostate cancer. More studies are needed for further validation.